Presentation of pulmonary tuberculosis in diabetics and response to anti-tuberculosis therapy - Waseem, Md Abdul; Zahera, Misba; Gopalakrishnaiah, V. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes and Tuberculosis are known to be mutually affective. In high tuberculosis and Diabetes burden country like ours, it is essential that we understand all the aspects concerning both these diseases individually and in mutual coexistence, in order to improve the management of this unhealthy partnership. Methods: This is a prospective hospital based observational study, in which 100 patients with coexisting Diabetes and new sputum confirmed pulmonary tuberculosis with no other comorbidities were included. Detailed history, examination and appropriate investigations were done evaluating the clinical and radiological presentation and treatment response in terms of sputum conversion at follow up visits. Results: Predominant symptoms were anorexia, fever and cough with sputum, majority with duration of more than 4 weeks. About half of them had diabetes duration of less than 1 year, most being newly diagnosed. All cases had upper lobe involvement; two thirds of them had lower lung field and multiple lobe involvement. Confluent consolidation, cavitary lesions and fluffy infiltrates were common. 27 of the 100 cases had a delayed sputum conversion. Longer duration of diabetes, maintenance on oral hypoglycaemic drugs alone and uncontrolled diabetes had delayed sputum conversion. Conclusions: Presenting symptoms of tuberculosis in diabetics is more or less similar to that in non-diabetics. Atypical radiological presentation with lower lung field involvement and confluent consolidation mimicking pneumonia is common. Delay in sputum conversion is common in dual disease and is increased with increasing DM duration and poor glycemic control. Better results may be obtained with insulin therapy.